Investment-cash flow sensitivity and financial constraints: Evidence from unquoted European SMEs - Mulier, Klaas; Schoors, Koen; Merlevede, Bruno (Journal of Banking & Finance, 2016)
We contribute to the financial constraints literature and the investment-cash flow sensitivity debate by defining a new and simple index of firm level financial constraints for unquoted European SMEs. Firms that are constrained according to our index pay higher interest rates on their debt. An exogenous financial supply shock reveals that our index also captures financial constraints in terms of the volume of credit. Our index outperforms existing indices in capturing financial constraints of unquoted SMEs. Finally, employing our proposed index to identify financially constrained firms and using firm-level employment growth as a control for investment opportunities, we find that constrained firms display the highest investment-cash flow sensitivities.